Coordination-variability and kinematics of misses versus swishes of basketball free throws - Mullineaux, D. R.; Uhl, T. L. (Journal of Sports Sciences, 2010)
Magnitudes and timings of kinematic variables have often been used to investigate technique. Where large inter-participant differences exist, as in basketball, analysis of intra-participant variability may provide an alternative indicator of good technique. The aim of the present study was to investigate the joint kinematics and coordination-variability between missed and successful (swishes) free throw attempts. Collegiate level basketball players performed 20 free throws, during which ball release parameters and player kinematics were recorded. For each participant, three misses and three swishes were randomly selected and analysed. Margins of error were calculated based on the optimal-minimum-speed principle. Differences in outcome were distinguished by ball release speeds statistically lower than the optimal speed (misses -0.12 ± 0.10m/s; swishes -0.02 ± 0.07m/s; P < 0.05). No differences in wrist linear velocity were detected, but as the elbow influences the wrist through velocity-dependent-torques, elbow-wrist angle-angle coordination-variability was quantified using vector-coding and found to increase in misses during the last 0.016s before ball release (P < 0.05). As the margin of error on release parameters is small, the coordination-variability is small, but the increased coordination-variability just before ball release for misses is proposed to arise from players perceiving the technique to be inappropriate and trying to correct the shot. The synergy or coupling relationship between the elbow and wrist angles to generate the appropriate ball speed is proposed as the mechanism determining success of free-throw shots in experienced players.